Elevated 18F-FDG accumulation in a malignant epithelioid angiomyolipoma: a case report and review of literature - Zhang, Li; Chen, Leqing; Deng, Yinqian; Chen, Huanyu; Wu, Yujun; An, Peng; Fan, Jun; Jiang, Dawei; Lan, Xiaoli; Cao, Wei (Frontiers in Oncology, 2025)
Epithelioid angiomyolipoma (EAML) is a tumor with malignant potential, as evidenced by its pathological features. Further investigation into its additional characteristics, particularly in imaging, is of great significance for non-invasive detection methods to understand its malignant potential. In this context, we present a case study of a 47-year-old male patient with a right renal EAML. The patient underwent nephrectomy but subsequently developed liver metastasis. Next-generation sequencing confirmed mutations of tuberous sclerosis 2 (TSC2) in both the primary and metastatic lesions. Consequently, the patient received maintenance treatment with the mTOR inhibitor, everolimus. However, treatment was discontinued after six months due to disease progression. Subsequent 18F-FDG PET/CT imaging revealed a large heterogeneous hypermetabolic mass in the liver, along with two other hypermetabolic metastases near the liver capsule. The patient’s prognosis was poor, with indicators such as TSC2 mutation, tumor necrosis, high Ki-67 expression, and α-SMA-negative fibroblasts. Despite reoperation, the patient still succumbed to disease progression. The occurrence of malignant metastatic EAML detected using 18F-FDG PET/CT imaging is infrequent. We conducted a comprehensive review of the relevant literature on 18F-FDG PET/CT imaging for EAML. Notably, this article emphasizes that elevated 18F-FDG uptake in EAML may serve as a novel indicator of malignant EAML.